Hubungan Tingkat Kecukupan Karbohidrat Dan Persen Lemak Tubuh Dengan Sindroma Pramenstruasi (PMS) Pada Remaja Putri - Shella Habibatul Illah Rahmadianta; Sri Adiningsih (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Premenstrual Syndromes are commonly found in many adolescent girls. There are several factors that contribute to the incidence of premenstrual syndrome such as hormonal change, nutritional status, food intake, and lifestyle.Objectives: The purpose of this study was analyzing correlation of sufficiency of carbohydrate and percentage fat body with premenstrual syndrome in female teenagers at SMA Negeri 4 BojonegoroMethods: The research used cross sectional study. The sample size was 110 female students in SMA Negeri 4 Bojonegoro. The data were collected by measuring percentage body fat to obtain percentage body fat variable; 2x24 hours estimated food recall to obtain of carbohydrate sufficiency; and Moos Menstrual Distress Questionnare (MDQ) for premenstrual syndrome cases. The data were analyzed using spearman test to find out correlation between carbohydrat sufficiency and percentage fat body intake towards premenstrual syndrome (PMS) in female teenagers. Result: The result of this study showed that there was correlation between sufficiency of carbohydrate) and Premenstrual Syndrome (p=0.010). Beside that, there was also a not correlation between percentage body fat) and Premenstrual Syndrome (PMS) (p= 0.642). Conclusions: There was correlation between levels of carbohydrate intake with premenstrual syndrome in female teenagers and there was not corelation between percentage fat body with premenstrual syndrome in female teenagers of Senior High School 4, Bojonegoro. Therefore, adolescent girls encouraged to increase carbohydrate intake to prevent the occurrence of premenstrual syndrome.ABSTRAK Latar Belakang: Sindroma Pramenstruasi (PMS) banyak melanda remaja putri. Terdapat beberapa faKtor yang berkontribusi terhadap kejadian sindroma pramenstruasi seperti perubahan hormonal, status gizi, asupan makan, dan gaya hidup.Tujuan: Tujian dari penelitian ini adalah untuk menganalisis hubungan tingkat kecukupan karbohidrat dan persen lemak tubuh dengan sindroma pramenstruasi (PMS) pada remaja putri di SMA Negeri 4 BojonegoroMetode: Penelitian ini dengan desaincross sectional. Populasi penelitian ini adalah siswi SMA Negeri 4 Bojonegoro. Hasil dari perhitungan random sampling didapat 110 siswi sebagai sampel. Pengumpulan data menggunakan pengukuran persen lemak tubuh untuk mendapatkan variabel persen lemak tubuh, pengisian form Estimated Food Recall 2x24 jam untuk mendapatkan variabel tingkat kecukupan karbohidrat.,dan menggunakan Moos Menstrual Distress Questionnare (MDQ) untuk mendapatkan variabel Sindroma Pramenstruasi. Data dianalisiss menggunakan uji spearman untuk mengetahui hubungan tingkat kecukupan karbohidrat dan persen lemak tubuh dengan sindroma pramenstruasi pada remaja putri .Hasil: Hasil penelitian ini menunjukkan ada hubungan antara tingkat kecukupan karbohidrat dengan sindroma pramenstruasi (p= 0,010) dan tidak ada hubungan antara persen lemak tubuh dengan sindroma pramenstuasi pada remaja putri (p= 0,642).Kesimpulan: Terdapat hubungan antara tingkat kecukupan karbohidrat dan persen lemak tubuh dengan kejadian sindroma pramenstruasi pada siswi di SMA Negeri 4 Bojonegoro. Oleh karena itu, remaja putri dianjurkan untuk mengonsumsi karbohidrat sesuai kecukupan untuk mencegah kejadian sindroma pramenstruasi.